Circadian clock regulates photoperiodic responses governed by distinct output pathways in the bean bug, Riptortus pedestris. Issue 6 (1st November 2016) - Omura, Shigeki; Numata, Hideharu; Goto, Shin G.
Abstract: Effects of RNA interference (RNAi) targeted against circadian clock genes on two distinct types of photoperiodic responses – ovarian development and lipid accumulation – were investigated in a bean bug Riptortus pedestris, to explore which physiological process in the photoperiodic response involved the circadian clock. Ovarian development and lipid accumulation are known to be regulated by distinct output pathways. Control insects showed clear photoperiodic responses; i.e. induction of ovarian development and suppression of lipid accumulation under long-day conditions, whereas opposite characteristics under short-day conditions. We found that RNAi directed against period, a negative element of the circadian clock, produced a long-day effect for both the ovarian development and lipid accumulation, while RNAi directed against Clock, a positive element of the circadian clock, produced a short-day effect for both, irrespective of photoperiod. These results indicate that the circadian clock comprised of these genes regulates a process governing both distinct photoperiodic responses.